Implementasi Software Cabri 3D terhadap Pemahaman Konsep Matematis Mahasiswa - Christa Voni Roulina Sinaga; Apriani Sijabat (Journal on Education, 2023)
The purpose of this study was to determine the implementation of Cabri 3D software on students' understanding of mathematical concepts. The type of this research is quasi-experimental research. One form of design used is the nonequivalent control group design. The instrument used in this research is an instrument to test the ability to understand mathematical concepts. The results obtained were that after implementing the Cabri application assisted learning in the experimental class, the average value of the pretest scores of student learning outcomes was an average of 75, while the pretest average value of the control class learning outcomes was 50. Posttest scores of student learning outcomes with an average -an average of 80, while the average value of the posttest control class learning outcomes is 72.5. This shows that the use of media assisted by the Cabri application in learning students' understanding of mathematical concepts is higher. Based on the average score of the student learning outcomes test, it can be seen that the experimental class is higher than the control class. This shows that the use of media assisted by the Cabri application in learning cubes and blocks has a significant effect on students' ability to understand mathematical concepts in geometric material.